2000
DOI: 10.1063/1.373005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of metalorganic chemical vapor deposition of (Ba,Sr)TiO3 thin films

Abstract: The metalorganic precursor chemistry was studied on Pt(111) surfaces in a O162 and O182 backgrounds. Using temperature programmed desorption (TPD) and static secondary ion mass spectrometry (SIMS). The precursor chemistry of Sr(thd)2 was found to be different on oxide covered Pt(111) surface as compared to the clean Pt(111) surface. In an oxygen ambient, TPD showed at least four different reaction processes which involved the removal of carbon from the precursor ligands on oxide covered Pt(111). In two of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…T he high‐permittivity (Ba,Sr)TiO 3 (BST) thin films have been intensively studied in recent years as a potential dielectric material for the development of capacitors in microwave devices and future ultra high‐density dynamic random access memories (DRAM) because of their low dielectric loss, high breakdown field strength, tunable dielectric constant, low leakage current density, and high reliability 1 . The present research interests in this class of high‐permittivity perovskite oxides are directed toward achieving improved performance of miniaturized BST capacitors by tuning the processing parameters, 2 reducing the leakage current density by suitable dopants, 3 fabricating composite or multilayer capacitors and superlattices with enhanced properties, 4 and adopting innovative procedures for the integration of high‐permittivity films directly on silicon (Si) 5 . Among the various factors that lead to high leakage current density in BST thin films, oxygen vacancy formation at the film/electrode interface has been identified as a major cause for current conduction and performance degradation of BST capacitors 6,7 .…”
Section: Introductionsupporting
confidence: 86%
“…T he high‐permittivity (Ba,Sr)TiO 3 (BST) thin films have been intensively studied in recent years as a potential dielectric material for the development of capacitors in microwave devices and future ultra high‐density dynamic random access memories (DRAM) because of their low dielectric loss, high breakdown field strength, tunable dielectric constant, low leakage current density, and high reliability 1 . The present research interests in this class of high‐permittivity perovskite oxides are directed toward achieving improved performance of miniaturized BST capacitors by tuning the processing parameters, 2 reducing the leakage current density by suitable dopants, 3 fabricating composite or multilayer capacitors and superlattices with enhanced properties, 4 and adopting innovative procedures for the integration of high‐permittivity films directly on silicon (Si) 5 . Among the various factors that lead to high leakage current density in BST thin films, oxygen vacancy formation at the film/electrode interface has been identified as a major cause for current conduction and performance degradation of BST capacitors 6,7 .…”
Section: Introductionsupporting
confidence: 86%
“…Although single-crystal substrates such as LaAlO 3 , MgO and SrTiO 3 have been adopted due to the good lattice match and low substrate dielectric loss, Si wafers have intrigued great interest in order to make multifaceted devices in the integrated microelectronics field [7][8][9]. Gao et al fabricated (0 0 1) BST film on platinized Si by metalorganic chemical vapor deposition and investigated a mechanistic study of MOCVD growth [10]. Padmini et al reported (0 0 1) texture BST film on platnized Si using RF magnetron sputtering and investigated the dielectric constant properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4(a) displays that the remnant polarization and coercive field of the films is 3.8 µCcm −2 , and 45 kVcm −1 respectively at 25 • C, and the films has high saturation of P − E hysteresis loop, and the nonlinear characteristics as good as that of the bulk BST films. We also found this P − E hysteresis loop slowly turns into a single straight line when the measurement temperature was raised from 25 • C to, which also indicates that the Tc of the films is diffuse below 35 • C. Similar phenomena have been observed in BST and BT films derived from MOCVD and RF magnetron sputtering [24]. Tahan et al attribute these phenomena to the effect of nanoscale grain size, as seen in the surface morphology [25].…”
Section: Resultsmentioning
confidence: 53%